Co-occurrence of avian rotavirus and bacterial pathogens in diarrheic poultry - ., SAVITA; KUSUMAKAR, A L; MALIK, Y P S; ., MINAKSHI; PRASAD, G (The Indian Journal of Animal Sciences, 2011)
Association of avian rotavirus, E. coli and Salmonella were studied in the present study. Results indicated that 11.68% samples obtained from 7 different fanus had mixed etiology for diarrhea, which included 5.19% (4 samples) of both E. coli and Salmonella and 6.49% (5 samples) of E. coli and avian rotavirus infections. Therefore, proper investigation should be made to know the causative agent of disease and only then treatment would be effective. Study emphasized the implementation of hygienic conditions on poultry farms as antimicrobial agents are not effective in the prevention of viral diseases. Â